2018
DOI: 10.4067/s0718-58392018000200266
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antioxidant activity of some apricot varieties at different ripening stages

Abstract: Apricot (Prunus armeniaca L.) is a fruit tree species widespread in Europe due to the high nutritional value of its fruit. In this study, the changes in the chemical composition of seven apricot cultivars were studied during three fruit ripening stages. Proximate composition (water content, ash, lipids, proteins, carbohydrates) was determined by official AOAC methods, macro-and microelements (potassium (K), calcium (Ca), magnesium (Mg), and iron (Fe)) were detected by atomic absorption spectroscopy (AAS), whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
4
11
0
1
Order By: Relevance
“…However, the value in this study is within the range found by Koh et al (2009), who used 80 commercial broccoli types for ascorbic acid analysis. Furthermore, similar to our results, higher ascorbic acid content in matured plant parts was previously reported in vegetables and fruits such as red pepper (Bhandari et al, 2013) tomatoes (Bhandari and Lee, 2016), broccoli (Vallejo et al, 2003), and apricot (Iordanescu et al, 2018). All the new-variety candidates showed relatively higher ascorbic acid content than the control cultivar in their respective developmental stages, suggesting their higher nutritional value.…”
Section: Variation In Ascorbic Acid Contentsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the value in this study is within the range found by Koh et al (2009), who used 80 commercial broccoli types for ascorbic acid analysis. Furthermore, similar to our results, higher ascorbic acid content in matured plant parts was previously reported in vegetables and fruits such as red pepper (Bhandari et al, 2013) tomatoes (Bhandari and Lee, 2016), broccoli (Vallejo et al, 2003), and apricot (Iordanescu et al, 2018). All the new-variety candidates showed relatively higher ascorbic acid content than the control cultivar in their respective developmental stages, suggesting their higher nutritional value.…”
Section: Variation In Ascorbic Acid Contentsupporting
confidence: 91%
“…All the genotypes showed similar trends in each assay with the lowest value being in immature and the highest value in commercial stage of broccoli florets (Figure 2). Similar higher antioxidant activities at matured stage was also observed in fruits such as apricot (Iordanescu et al, 2018). However, antioxidant activities were dependent on the genotype.…”
Section: Variation In Antioxidant Activitiessupporting
confidence: 74%
“…The values ranged between 0.30 g/100 g fresh weight (FW) (A7) and 0.88 g/100 g FW (A1). The crude oil contents of many edible fruits are usually lower than 2%, and vary considerably depending on the climate, variety, geographical origin, harvest year, and the methods of cultivation [ 3 , 19 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Apricots are good sources of minerals, with potassium as the most important ion (1.5–1.7%), followed by calcium (0.06–0.26%) and magnesium (0.04–0.075%) [ 8 , 19 ]. Moreover, a daily consumption of 3–4 fresh apricots may supply the daily requirement of K, Mg, Fe, Se, and Mn and half of P and Zn for an average adult [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…After which, it was centrifuged at 4°C, 7000 × g for 10 min, and the ltrate was collected. Ten milliliters of the ltrate were titrated with 2,6-dichlorophenol indophenol dye [21] and the volume of the titrant was recorded. Ten milliliters of 20 g/L oxalic acid solution were used as a blank.…”
Section: Ascorbic Acidmentioning
confidence: 99%